Economic Influence of Cooperatives Among Small Farmers: A Study of The Southern Macro-Region of Peru on Agricultural Exports to Brazil by Land - Miguel PANEZ – BENDEZU (Communications of International Proceedings, 2022)
In the analysis of the food aid program of the World Food Program about economic and family implications of the pandemic on food security, the possible effect of COVID-19 on the poorest people in the world stands out. In this sense, measures are required to ensure the maintenance of food supply chains to mitigate the risk of shocks that can affect the world, especially the poor and most vulnerable people. In the face of these risks, the Food and Agriculture Organization (FAO) urges countries to support the ability of small farmers to increase food production, keep the wheels of national supply chains turning and maintain the global food trade.
Keywords: agricultural exports; associativity; small farmer; integration; Brazil; Peru